Integrated Digital Learning Tools to Enhance Student’s Mathematical Problem Solving Skills - Happy, Nurina; Rismawan, Rahmad; Santosa, Tomi Apra; Aprianto, Muchammad Chusnan; Dewanto, Dewanto (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
In the era of digital transformation, integrating technology into mathematics education has become an essential strategy for developing higher-order thinking and problem-solving skills among students. This study investigates the effectiveness of Integrated Digital Learning Tools (IDLT) in enhancing students’ mathematical problem-solving abilities across various cognitive dimensions. The research adopts a quasi-experimental design involving 120 secondary school students divided into experimental and control groups. The experimental group engaged in digital-based learning activities using an integrated platform that combines interactive simulations, adaptive learning analytics, and collaborative problem-solving modules, while the control group received conventional instruction. Data were collected through standardized mathematical problem-solving tests, learning engagement surveys, and classroom observations. The results revealed a significant improvement in the experimental group’s performance, particularly in the stages of problem identification, strategy formulation, and solution verification. Moreover, the integration of digital learning tools fostered metacognitive awareness and increased student motivation toward mathematics learning. These findings suggest that the implementation of IDLT can serve as a pedagogical innovation that supports personalized and inquiry-based learning environments. The study concludes that a well-designed digital ecosystem has the potential to bridge the gap between abstract mathematical concepts and real-world application, thereby promoting 21st-century learning competencies.